Comparative analysis of two oral contrast agent volumes for computed tomography enterography in crohn’s disease patients - Renosto, Fernanda Lofiego [UNESP]; de BARROS, Jaqueline Ribeiro [UNESP]; Bertoldi, Guilherme A.; Marrone, Sergio Ribeiro [UNESP]; Sassaki, Ligia Yukie [UNESP]; Saad-Hossne, Rogerio [UNESP] (FapUNIFESP (SciELO), 2021)
Background – Crohn’s disease (CD) is an inflammatory bowel disease characterized by a chronic and recurrent inflammation of the gastrointestinal tract caused by an interaction of genetic and environmental factors. Objective – To compare the quality and acceptance of two different oral contrast volumes for computed tomography enterography in Crohn’s disease patients. Methods – A cross-sectional study was conducted in 58 consecutive Crohn’s disease patients who randomly received an oral contrast agent composed of 78.75 g polyethylene glycol diluted in either 1,000 mL or 2,000 mL of water. An examination was performed to evaluate the presence of inflammation or complications in the small bowel. The variables included the quality of intestinal segment filling and luminal distension, and oral contrast agent acceptance and tolerance in the patients. Statistical analysis included descriptive statistics and association tests. Results – A total of 58 patients were assessed, in which 58.6% were female, 34.5% exhibited clinically-active disease, and 63.8% were receiving biologic therapy. As for comparative analysis between the two different volumes of oral contrast, no statistically significant difference was found regarding bowel loop filling (P=0.58) and adequate luminal distension (P=0.45). Patients who received a larger volume (2,000 mL) exhibited side-effects more frequently (51.7% vs 31.0%; P=0.06) and had greater difficulty ingesting the agent (65.5% vs 37.9%; P=0.07) compared with a volume of 1,000 mL. Conclusion – The quality of computed tomography enterography was not influenced by the contrast volume. However, acceptance and tolerance were better in the 1,000 mL group.
Análise comparativa de dois volumes diferentes de agente de contraste oral para enterografia por tomografia computadorizada em pacientes com doença de crohn.
Keywords: Contrast agent; Crohn’s disease; Polyethylene glycol; Tomography